(untitled) (Global Journal of Science Frontier Research, 2024)
This paper is concerned with frontiers as spaces of disputed, ceded, suspended, or imposed forms of rule, that challenge the integrity of bounded territorial polities and their jigsaw puzzle-limits. In recent decades, frontiers have received increased attention, perhaps due to the growing importance "marginal" and "ungoverned spaces" have acquired within the global economy. In spite of their enormous diversity of climates, landscapes and societies, frontiers in Latin America have historically been described and intervened in surprisingly similar ways. The ’idea’ of the frontier is here so intertwined with the reality of these places, that they have become indistinguishable. This article explores the production of frontiers, more than as a type of space, as an object of common sense and intervention. From an ontological point of view, its aim is to problematize the way frontiers are produced and enacted as an object, constituted and enacted in practice, by dissecting its constitutive practices: what is categorized as a frontier, how is it categorized; and its constitutive relations: the conditions and possibilities created by the frontier that empower certain groups and create new systems of access and control of land and resources.